Characterization of the bacterial microbiome of non-hematophagous bats and associated ectoparasites from Brazil - André, Marcos Rogério; Ikeda, Priscila; Lee, Daniel Antônio Braga; do Amaral, Renan Bressianini; Carvalho, Lucas Amoroso Lopes; Pinheiro, Daniel Guariz; Torres, Jaire Marinho; de Mello, Victória Valente Califre; Rice, Gregory K.; Cer, Regina Z.; Lourenço, Elizabete Captivo; Oliveira, Carisa Elisei; et al. (Frontiers in Microbiology, 2023)
Bats, along with their ectoparasites, harbor a wide diversity of symbiotic and potential pathogenic bacteria. Despite the enormous diversity of bats (181 species), few studies aimed to investigate the bacterial microbiome of Brazilian chiropterans and associated ectoparasites. This study aimed to characterize the bacterial microbiome of non-hematophagous bats and associated Streblidae flies and Macronyssidae and Spinturnicidae mites in the state of Mato Grosso do Sul, midwestern Brazil. For this purpose, oral and rectal swabs were collected from 30 bats (Artibeus lituratus [n=13], Artibeus planirostris [n=9], Eptesicus furinalis [n=5], Carollia perspicillata [n=2], and Platyrrhinus lineatus [n=1]). In addition, a total of 58 mites (15 Macronyssidae and 43 Spinturnicidae) and 48 Streblidae bat flies were collected from the captured bats. After DNA extraction and purification, each sample's bacterial composition was analyzed with metagenomic sequencing. The microbiome composition of both oral and rectal bat swab samples showed that Gammaproteobacteria was the most abundant bacterial class. Spiroplasma, Wolbachia and Bartonella represented the most abundant genera in Streblidae flies. While Wolbachia (Alphaproteobacteria) was the most abundant genus found in Spinturnicidae, Arsenophonus (Gammaproteobacteria) was found in high abundance in Macronyssidae mites. In addition to characterizing the microbiome of each sample at the class and genus taxonomic levels, we identified medically significant bacteria able to infect both animals and humans in oral (Streptococcus and Anaplasma) and rectal swabs (Enterobacter, Klebsiella, Escherichia, Enterococcus, Streptococcus), Macronyssidae (Anaplasma, Bartonella, Ehrlichia) and Spinturnicidae (Anaplasma, Bartonella) mites as well as Streblidae flies (Spiroplasma, Bartonella). Besides expanding the knowledge on the bacterial microbiome of non-hematophagous bats and Streblidae flies from Brazil, the present work showed, for the first time, the bacterial community of bat-associated Macronyssidae and Spinturnicidae mites.